Pemikiran Pembaharuan Pendidikan K.H Ahmad Dahlan di Indonesia: Penelitian - Yusril (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Educational reform in Indonesia is inextricably linked to the figure of K.H. Ahmad Dahlan, through the Muhammadiyah organization. The founding goal of Muhammadiyah was to interpret the verses of the Qur'an, first revealed through the Prophet Muhammad. With the word "Iqra," meaning "read," K.H. Ahmad Dahlan stated that seeking knowledge is an obligation. The purpose of this research is to develop, refine, and examine the material in a complex and in-depth manner. The research method is library research, collecting data and information from various relevant sources. The existing educational problems among indigenous people are educational underdevelopment due to a dualism in educational models with conflicting roots and personalities. Educational reform began as a synthetic effort, combining religious and general knowledge; modernism, adapting to developments in science and technology; and reconstructionism, with a perspective of rebuilding to ensure the survival and continued acceptance of traditions within a society; they must be rebuilt. Historically, these reform efforts emerged to create a society with noble character and progressive education.